2015
DOI: 10.1086/680553
|View full text |Cite
|
Sign up to set email alerts
|

Plastid DNA Homogeneity inCeltis australisL. (Cannabaceae) andNerium oleanderL. (Apocynaceae) throughout the Mediterranean Basin

Abstract: Editor: Alan W. Meerow Premise of research. Riparian plants are highly dependent on water sources; consequently, general climatic conditions are less important to these taxa relative to woodland and shrubland species. This leads to interesting research questions regarding riparian plant taxa. Research on phylogeography of Mediterranean riparian tree and shrub species is scarce. In this article, we investigated the plastidial genetic diversity in Celtis australis L. (hackberry) and Nerium oleander L. (oleander)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…These results contrast with the higher plastid diversity observed in other Mediterranean trees like Erica arborea L., O . europaea or Myrtus communis L. (Besnard, Terral, & Cornille, ; Désamoré et al, ; Migliore et al, ); but are congruent with the low plastid variation observed in Laurus nobilis L. (Rodriguez‐Sanchez, Guzmán, Valido, Vargas, & Arroyo, ) and even higher than in Celtis occidentalis L. and Nerium oleander L. (Mateu‐Andres et al, ). Nuclear and plastid markers therefore indicate low levels of allelic richness for the carob tree which are consistent with a strong decline scenario.…”
Section: Discussionmentioning
confidence: 67%
“…These results contrast with the higher plastid diversity observed in other Mediterranean trees like Erica arborea L., O . europaea or Myrtus communis L. (Besnard, Terral, & Cornille, ; Désamoré et al, ; Migliore et al, ); but are congruent with the low plastid variation observed in Laurus nobilis L. (Rodriguez‐Sanchez, Guzmán, Valido, Vargas, & Arroyo, ) and even higher than in Celtis occidentalis L. and Nerium oleander L. (Mateu‐Andres et al, ). Nuclear and plastid markers therefore indicate low levels of allelic richness for the carob tree which are consistent with a strong decline scenario.…”
Section: Discussionmentioning
confidence: 67%
“…Fernández‐Mazuecos & Vargas (2011) postulated that Quaternary climate changes in the Mediterranean Basin caused a massive extinction of mainland populations. This extinction may have resulted in a dramatic genetic bottleneck, followed by recent expansion from some refugia, a pattern also described in other Mediterranean plants (Vendramin et al, 2008; Mateu‐Andrés et al, 2015). Nevertheless, the location of mainland refugia remains unknown for C. monspeliensis .…”
Section: Introductionmentioning
confidence: 61%
“…Traits refer to the following character states: SH = shrub versus PH = tree/woody climber; FD = deciduous, semi‐deciduous or facultative deciduous versus EV = evergreen sclerophylls; LL = large‐leaved (typically >5 cm long or >5 cm 2 in size) versus SL = small leaved. (a) Bello (2015), (b) Viruel et al (2020), (c) Coello et al (2020), (d) Fernández‐Mazuecos and Vargas (2010), (e) Désamoré et al (2011), (f) Rodríguez‐Sánchez et al (2009), (g) Kondraskov et al (2015), (h) Migliore et al (2012), (i) Besnard et al (2013), (j) García‐Verdugo et al (unpublished data), (k) Mateu‐Andrés et al (2015); (l) García‐Verdugo et al (2015, 2020), (m) Vendramin et al (2008), (n) Saladin et al (2017), (o) Vitelli et al (2017), (p) Mateu‐Andrés et al (2013), (q) Chen et al (2014) and (r) Grassi et al (2006).…”
Section: Resultsmentioning
confidence: 96%